The role of the rural tourism experience economy in place attachment and behavioral intentions - Loureiro, S. M. C. (International Journal of Hospitality Management, 2014)
This study aims to empirically explore the effect of the experience economy on place attachment and behavioral intentions through emotions and memory. To do so, the rural tourism context was selected as it not only provides small accommodation units in the countryside, but is also related to a set of possible activities involving both passive and active participation by guests. The survey was conducted using a self-administered questionnaire distributed to individuals experiencing rural holidays in the South of Portugal. A convenience sample of participants, resulting on 222 usable questionnaires, was employed to test the model. The partial least squares (PLS) approach was used to treat the data. The findings demonstrated the role of pleasant arousal and memory as mediators between experience and behavioral intentions. An excited and pleased guest is more likely to memorize the experience. Nevertheless, the effect of pleasant arousal and memory on place attachment was not proven. The findings also lead to managerial implications, limitations and suggestions for future research.